Development of a Web-Based Scheduling Information System with Agile Methodology Using Next.js and Supabase - Mushaf; Muh Dimas Januardi Nur; Nurul Ilmi; Nurfadilah; Ahmad Khairul Shiddiq (Journal of Embedded Systems, Security and Intelligent Systems, 2025)
This study analyzes the development and impact of FOKUS!, a web-based scheduling application designed to help individuals, particularly students and professionals, manage time and tasks effectively. The system was built using an Agile approach across three sprints, involving UI/UX design, backend setup with Next.js and Supabase, and implementation of task management and notification features. Results from White Box testing indicated 100% frontend code coverage, with stable component rendering and logic validation. Black Box testing confirmed that core features—registration, login, task CRUD, and reminders— functioned as intended. Feasibility studies showed that the system is viable technically, economically, and organizationally. Users appreciated the intuitive interface and real-time synchronization. The system is expected to positively impact productivity and time efficiency. Future improvements include enhancing backend testing, integrating external calendar services, and conducting user acceptance testing to ensure a better user experience.